Analysis and Implementation of Bandwidth Management on Wireless Local Area Network Internet Using the PCQ Method at SMAN 1 Mawasangka Tengah - M, Nurhayati; Al Jum'ah, Muhammad Naim; Mardianto (CV. Digital Innovation, 2025)
With the rapid development of internet network technology, bandwidth management has become crucial, especially in networks with many users SMAN 1 Mawasangka Tengah has a Wi-Fi network used by teachers and students, but the network often experiences disruptions due to the lack of proper bandwidth management. This research aims to analyze and implement bandwidth management using the Per Connection Queue (PCQ) method to automatically and evenly allocate bandwidth to all users. Testing was conducted by comparing network performance before and after the implementation of bandwidth management, with QoS tests including throughput, delay, and packet loss. The results show that after implementing the PCQ method, the network's performance became more stable with a more even distribution of bandwidth. This is proven by an increase in average throughput for download activities from 8,690 kbps to 12,316 kbps, and video streaming from 986.33 kbps to 1,607.33 kbps. Delay decreased from 1.1 ms to 0.71 ms for downloads, and video streaming from 9.85 ms to 5.02 ms. Packet loss also decreased from 4.43% to 0% for downloads, and video streaming from 7.73% to 0.1%. In conclusion, the PCQ method is effective in addressing network stability and bandwidth management issues at SMAN 1 Mawasangka Tengah.